Surface modifications of Ti alloy with tunable hierarchical structures and chemistry for improved metal–polymer interface used in deepwater composite riser - He, Peigang (2016)
Ti-based fiber reinforced plastic (Ti-FRP) composites have attracted increasing attentions in the marine and offshore applications due their excellent specific mechanical and physical properties. Among those, interface issues play important role to determine the failure modes of the hybrid composites. In this paper, tunable hierarchical structures and oxidation states on Ti alloy (Ti6Al4V) were achieved via physical and chemical surface treatment techniques including sandblasting, anodization, etching and annealing. Wetability and interfacial bonding strength between the treated Ti alloy surfaces and epoxy resin were systemically investigated in consideration of surface microstructures, oxidation states of Ti, and possible chemical reaction between oxidized Ti and amine. After the combined treatments, the epoxy-adhered specimen showed fully cohesive failure mode in epoxy with the highest shear strength and work of fracture. The great increase in the shear bonding strength was attributed to the nano- to macro-scale hierarchical structure on the Ti alloy surface which resulted in the enhanced adhesive strength between epoxy and adherend in terms of the excellent wettability, significant interfacial chemical reaction and reasonable mechanical interlocking.